Communication in the 21st Century: The Effect of internet celebrity as the communication source in influencing generation Z purchase intention - Mun, Soon Lam; Si, Yan Tan; Ying, San Lim; Tuan, Hock Ng (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current corporate landscape is characterized by fierce rivalry, prompting marketers to actively seek strategies to effectively differentiate themselves amidst the abundance of information in the digital realm. One current marketing strategy involves the engagement of online influencers, also known as Internet celebrities, to effectively disseminate information and encourage the intended consumer base to purchase the items offered by their respective companies. In the modern day, it has been customary for individuals who have gained fame through online platforms to create video content with the intention of engaging and influencing their audience on various social media platforms. This practice has now become a norm. Hence, the primary objective of this research is to examine the impact of Internet celebrity on consumer purchase intention, with a specific focus on the Generation Z demographic. The study involved the recruitment of 200 participants from the Generation Z demographic. Data was collected using an online questionnaire that employed 5-point Likert rating scales. The research was conducted by gathering feedback from a sample of 200 respondents belonging to Generation Z. Data collection was conducted through the utilisation of an online questionnaire using 5-Likert rating scales. The findings of the study revealed a significant correlation between credibility and meaning transfer and their impact on purchase intention. The research findings of this study provide marketers and scholars with valuable insights into the ways in which Internet superstars might employ persuasive messaging to impact the purchasing intentions of Generation Z.